Association of High-Speed Rail and Tuberculosis Transmission in Newly Integrated Regions: Quasi-Experimental Evidence from China - Yahong Liu; Chengxiang Tang; Tao Bu; Daisheng Tang (Frontiers Media S.A., 2021)
Objectives: The spread of tuberculosis (TB) is related to changes in the social network among the population and people's social interactions. High-speed railway (HSR) fundamentally changed the integrated market across cities in China. This paper aims to examine the impact of HSR on TB transmission in newly integrated areas.Methods: By exploiting the opening and operation of the first HSR in Sichuan province as a quasi-natural experiment, we have collected and used the economic, social, and demographic data of 183 counties in Sichuan province from 2013 to 2016.Results: The new HSR line is associated with a 4.790 increase in newly diagnosed smear-positive TB cases per 100,000 people among newly integrated areas. On average, an additional increase of 34.178 newly diagnosed smear-positive TB cases occur every year in counties (or districts) covered by the new HSR.Conclusion: HSR development has significantly contributed to the transmission of TB. The public health system in China needs to pay more attention to the influences of new, mass public transportation.